Unveiling deep-sea benthic biodiversity in the northern South China Sea through environmental DNA metabarcoding - Yaqin Huang; Kun Liu; Qianyong Liang; Heshan Lin; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Xuebao He; Zhongbao Li (Frontiers in Marine Science, 2026)
The northern South China Sea hosts highly heterogeneous deep-sea habitats, dotted with numerous active cold seeps and associated chemosynthetic ecosystems, while the Qiongdongnan Basin represents one of the most important natural gas hydrate accumulation regions in this area. Benthic fauna are core components sustaining deep-sea ecosystem stability and function, yet the biodiversity and community structure of benthic assemblages in this hydrate-rich basin remain poorly documented, creating a critical knowledge gap that hinders the ecological risk assessment and sustainable exploitation of local gas hydrate resources. Using environmental DNA (eDNA) metabarcoding, this study systematically investigated benthic biodiversity, community structure, and underlying assembly mechanisms across three representative habitat types in the Qiongdongnan Basin: cold seeps (CSs), gas hydrate stable zones (GHSZs), and non-gas hydrate stable zones (Non-GHSZs). A total of 334 benthic faunal species belonging to 275 genera, 167 families, 78 orders, 29 classes, and 19 phyla were recovered across all samples. Benthic genus richness peaked in GHSZs (191 genera), followed by CSs (184 genera), and was lowest in Non-GHSZs (176 genera). Community composition exhibited clear habitat-specific partitioning: GHSZ assemblages were dominated by Nematoda, Annelida, and Nemertea; Non-GHSZ assemblages were dominated by Nematoda, Echinodermata, and Annelida; and CS assemblages were dominated by Annelida, Echinodermata, and Mollusca. PERMANOVA confirmed significant overall differences in benthic community composition among the three habitats, with pairwise tests identifying CSs as the primary driver of inter-habitat dissimilarity. Integrated analyses using neutral community models and null models further revealed that deterministic processes. particularly variable selection, overwhelmingly governed benthic community assembly, while stochastic processes such as ecological drift and homogenizing dispersal played only a minor role. Environmental driver analysis indicated that benthic community variation in non-seep habitats (GHSZs and Non-GHSZs) was primarily modulated by sediment grain-size parameters and bottom-water salinity, whereas CS community structure was strongly correlated with sediment total organic carbon, sand content, and local meiobenthos density. This study provides a systematic eDNA-based assessment of benthic biodiversity across contrasting deep-sea habitats in the hydrate-bearing Qiongdongnan Basin and contributes a regional biodiversity baseline to support future ecological conservation, environmental impact assessment, and sustainable natural gas hydrate exploration and exploitation.

Thermal threshold triggers hepatic immune reprogramming and oxidative exhaustion in large yellow croaker Larimichthys crocea - Caoqun Zheng; Rabia Zeb; Ronghui Zheng; Chao Fang; Junwei You; Kun Liu; Heshan Lin; Jun Bo (Marine Environmental Research, 2026)

Enhancing coastal resilience with nature-based solutions: Policy-driven restoration of a high-energy beach (Changle Airport Beach, China) - Shasha Liu; Fan Yu; Feng Cai; Heshan Lin; Degang Jiang; Patryk Sitkiewicz; Yanyu He; Hang Yin; Michael Wagreich; Ivica Vilibić (Ocean & Coastal Management, 2026)

Screening of high-risk phytoplankton species and mechanisms of bloom outbreaks in temperate waters adjacent to a nuclear power plant - Youyin Ye; Xiuwu Sun; Heshan Lin; Yu Wang; Yanghang Chen; Qianqian Zhou; Baohong Chen; Xuebao He; Peng Xiang; Hui Lin (Marine Pollution Bulletin, 2026)

Size-independent thermal tolerance enhancement in hybrid Abalone (Haliotis discus hannai × H. fulgens) under high-temperature acclimation - Shuyi Zhang; Jianfeng Mou; Yaqin Huang; Ronghui Zheng; Jun Bo; Youling Ye; Kun Liu; Heshan Lin (Aquaculture International, 2025)

Mapping the research framework and key trends of coral reefs in the South China Sea - Junhui Chen; Fei Tang; Heshan Lin; Bo Huang; Xueping Lin (Frontiers in Marine Science, 2025)
The South China Sea, a key biodiversity hotspot in the Central Indo-Pacific, hosts a rich array of coral reef species and marine life but faces growing threats from climate change and human activities. This study systematically analyzes coral reef research in the region using a bibliometric analysis of records from the Web of Science Core Collection. The analysis highlights the diverse roles of contributing countries and their collaborations, with China emerging as a significant contributor to the regional scientific output. Our findings categorize the research into five principal themes through text mining and bibliographic coupling: (1) fundamental physical-biological interactions within reef systems, (2) biodiversity and symbiotic relationships in response to environmental stress, (3) climatic influences and the adaptive responses of reef systems, (4) conservation strategies and management practices for reef resilience, and (5) remote sensing and algorithmic approaches for reef mapping and monitoring. The discussion addresses regional challenges, outlines the identified research framework, and details key trends in South China Sea coral reef research, thereby providing essential information to guide future development and conservation efforts.

Distribution and Relationship of Radionuclides and Heavy Metal Concentrations in Marine Sediments from the Areas Surrounding the Daya Bay Power Plant, Southeast China - Chengpeng Huang; Yunpeng Lin; Haidong Li; Binxin Zheng; Xueqiang Zhu; Yiming Xu; Heshan Lin; Qiangqiang Zhong; Fangfang Shu; Mingjiang Cai; Yunhai Li (Journal of Marine Science and Engineering, 2025)
Radionuclides and heavy metals pose potential risks to marine ecosystems and human health. Daya Bay, the site of China’s first commercial nuclear power plant, has experienced significant anthropogenic impacts, yet the extent of radionuclide and heavy metal contamination remains unclear. Nineteen surface sediment samples were collected in January 2024 and analyzed for natural (210Pb, 228Th, 226Ra, 228Ra, and 40K) and anthropogenic (137Cs) radionuclides, heavy metals (Cu, Pb, Zn, Cd, Cr, Mn, Hg, and As), grain size, and total organic carbon (TOC). The surface sediments of Daya Bay were predominantly fine-grained, with TOC levels ranging from 0.41% to 1.83%, influenced significantly by riverine input from the Dan’ao River. Natural radionuclides exhibited distinct spatial patterns: 210Pb and 228Th activity levels were higher in fine-grained sediments, and correlated with TOC, indicating adsorption and sedimentation controls. In contrast, anthropogenic 137Cs activity was low and showed no significant impact from the nuclear power plant. Notably, the absence in the samples of key anthropogenic radionuclides typically associated with nuclear power plant operations further confirmed the negligible impact of the power plant on local sediment contamination. The results indicated that the baseline levels of both natural and anthropogenic radionuclides and heavy metals were predominantly influenced by natural processes and local anthropogenic activities rather than the operation of the nuclear power plant. This study establishes critical baselines for radioactivity and heavy metals in Daya Bay, underscoring effective pollution control measures and the resilience of local ecosystems despite anthropogenic pressures.

Multiple environmental gradients shape the functional structure of macrobenthic communities across the Pacific Arctic shelf - Kun Liu; Yaqin Huang; Weibo Wang; Jianfeng Mou; Junhui Lin; Shuyi Zhang; Longshan Lin; Jun Sun; Zhongyong Gao; Heshan Lin; Xuebao He (Science of The Total Environment, 2024)

Key environmental parameters and numerical prediction model of jellyfish bloom in Qingchuan Bay Nuclear Power Plant, China - Zichun Shen; Wen Fang; Zhenxin Yu; Xiaoyin Chen; Zhiyu Su; Wen Yu; Heshan Lin (Marine Environmental Research, 2024)

Quantitatively characterize the response of the hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) under elevated temperature stress - Ronghui Zheng; Xingzhang Lai; Chao Fang; Heshan Lin; Yixin Huang; Jiang Zheng; Jun Bo (Marine Environmental Research, 2024)

A Spatial–Temporal Analysis and Multi-Scenario Projections of Carbon Sequestration in Sea Islands: A Case Study of Pingtan Island - Siyu Chen; Ming Xu; Heshan Lin; Fei Tang; Jinyan Xu; Yikang Gao; Yunling Zhuang; Yong Chen (Journal of Marine Science and Engineering, 2024)
As an indispensable part of the marine ecosystem, the health status of the sea affects the stability and enhancement of the overall ecological function of the ocean. Clarifying the future land and sea utilization pattern and the impacts on the carbon stocks of island ecosystems is of great scientific value for maintaining marine ecological balance and promoting the sustainable development of the island ecosystem. Using Pingtan Island as an example, we simulate and predict changes in island utilization and carbon stocks for historical periods and multiple scenarios in 2030 via the PLUS-InVEST model and the marine biological carbon sink accounting method. The results show that (1) from 2006 to 2022, the carbon stock of Pingtan Island decreased by 7.218 × 104 t, resulting in a cumulative economic loss of approximately USD 13.35 million; furthermore, from 2014 to 2018, the implementation of many reclamation and land reclamation projects led to a severe carbon stock loss of 6.634 × 104 t. (2) By 2030, the projected carbon stock under the three different policy scenarios will be greater than that in 2022. The highest carbon stock of 595.373 × 104 t will be found in the ecological protection scenario (EPS), which will be 4.270 × 104 t more than that in 2022. With the strong carbon sequestration effect of the ocean, the total social carbon cost due to changes in island utilization is projected to decrease in 2030. (3) The factors driving changes in island utilization will vary in the design of different future scenarios. The results of this study not only provide a solid scientific basis for the sustainable development of island areas, but they also highlight the unique contribution of islands in the field of marine ecological conservation and carbon management, contributing to the realization of the dual-carbon goal.

Thermal Tolerance of Spotted Sea Bass (Lateolabrax maculatus) and Pearl Gentian Grouper (Epinephelus fuscoguttatus Female × E. lanceolatus Male) in Different Environmental Temperatures - Heshan Lin; Yaqin Huang; Kun Zhang; Jun Bo; Ronghui Zheng; Youling Ye; Kun Liu (Fishes, 2023)
Seawater cooling is the most common way to cool down nuclear power plants. However, the thermal drainage of nuclear power plants results in sharp rises in local seawater temperatures and, therefore, affects fisheries and ecologies. Therefore, evaluating the thermal tolerance of marine organisms not only provides further insight into their biological characteristics but also holds significant importance for the site selection and construction of nuclear power plants. This study investigated the thermal tolerance of spotted sea bass (Lateolabrax maculatus) and pearl gentian grouper (Epinephelus fuscoguttatus female × E. lanceolatus male) using the critical thermal maximum method. The environmental temperatures for spotted sea bass and grouper in spring, summer, autumn, and winter were 21.6/23 °C, 26.5/25.9 °C, 25.0/25.9 °C, and 14.5/16.6 °C, respectively. Under four seasonal conditions, different temperature rise rates of +2 °C, +4 °C, +6 °C, and +8 °C per hour were set. The maximum critical temperature, initial lethal temperature, absolute lethal temperature, and semi-lethal temperature were recorded for both fish species. The results show that the rates of temperature increase did not affect the thermal tolerance of either fish species. In all seasons, the fish experienced rapid death once they reached the initial lethal temperature. However, there was a significant correlation of season with thermal tolerance in both fish species. For spotted sea bass, the semi-lethal temperature in summer reached about 40 °C, while in winter it was about 35 °C. For pearl gentian grouper, the semi-lethal temperature in summer reached about 40 °C, while in winter, it was about 38 °C. These results remind us that these two fish species have a limited ability to adapt to rapid temperature rises, but appropriate acclimation temperatures can effectively improve their thermal tolerance. Therefore, it is necessary to further consider the potential impacts on these fish species during the site selection and construction process of nuclear power plants.

Resource recovery from textile wastewater: Dye, salt, and water regeneration using solar-driven interfacial evaporation - Shiwei Lin; Heshan Qi; Peiyu Hou; Kai Liu (Journal of Cleaner Production, 2023)

Biofouling characteristics in Xinghua Bay of Fujian, China - Heshan Lin; Yaqin Huang; Yingyue Lin; Shuyi Zhang; Shihao Yu; Kun Liu; Jianfeng Mou; Junhui Lin; Xuebao He; Sujing Fu; Weijie Xie; Zhongbao Li (Frontiers in Marine Science, 2023)
Biofouling is one of the main factors affecting the efficiency and safety of cooling water systems in coastal nuclear power plants. Understanding the population dynamics, succession rules and cumulative effects of major fouling organisms is the basis for targeted prevention and control. A 1-year simulated concrete panel test was conducted from December 2020 to November 2021 in Xinghua Bay, China. A total of 78 species of fouling organisms were recorded by combining the monthly, seasonal, semiannual, annual and monthly cumulative panels, and the community composition was dominated by nearshore warm-water species, making for a typical subtropical inner bay-type community. The fouling organisms had a peak attachment period from June to October. Significantly more attachment was observed during summer (from June to August) than during the other three seasons. The attachment amount in the second half-year (from June to November) was much higher than that in the first half-year (from December to May). The attachment thickness, density, and biomass of the bottom summer panels reached 20 cm, 105,150 ind./m 2 , and 19,274.50 g/m 2 , respectively, while those of the bottom annual panels were 40 cm, 27,300 ind./m 2 , and 17,762.50 g/m 2 , respectively. The dominant fouling organisms with calcified shells mainly included Amphibalanus reticulatus and Pernaviridis . These species had high attachment amounts,could accumulate attachments for a long time, and even might cause secondary blockage, making them the most detrimental to the safety of a cooling system. Moreover,the seasonal upward growth of hydroids and bryozoans can also significantly reduce the efficiency of cooling water intake. We suggest that targeted prevention and control should be carried out according to the larval attachment period of different dominant groups of fouling organisms during June-October, which can greatly improve the prevention and control efficiency. Strengthening the research on the biological cycle phenomenon of the main species and their main environmental impact factors, and establishing a scientific and effective early-warning model are the governance direction of formulating and implementing scientific pollution prevention and control in the future.

Efficient PPCPs degradation by self-assembly Ag/Ti3C2@BiPO4 activated peroxydisulfate with microwave irradiation: Enhanced adsorptive binding and radical generation - Shuo Li; Fanxue Lin; Heshan Zheng; Yongjie Zheng; Baogang Zhang; Jun Ma; Jun Nan (Chemical Engineering Journal, 2023)

Potential risk from and prevention of phytoplankton outbreaks in blocking the cooling water system in a nuclear power plant on the Southeast China coast - Yu Wang; Xiaoyin Chen; Yingyue Lin; Shuyi Zhang; Lin Chang; Xiaoming Tang; Peng Xiang; Heshan Lin (Frontiers in Marine Science, 2022)
The invasion or aggregation of marine biota in coastal waters has become a common problem, threatening the safety of cooling water systems in the context of environmental and climate changes. However, studies on issues of coastal nuclear power plants from the view of marine ecology have mostly focused on the thermal effluent, entrainment effect on organisms, residual chlorine, radioactivity, etc. There is a lack of information on the safety of cooling water systems in nuclear power plants blocked by marine biota. Based on field and historical datasets, this study screened phytoplankton species that may potentially block the cooling water system of the Fuqing nuclear power plant on the Southeast China coast, identified the phytoplankton risk and a risk calendar, and established a catalog of risk phytoplankton species for the cooling water system. The screening criteria were simultaneously required as follows: (1) particle size of cells or group >2000 μm; (2) phytoplankton bloom or aggregation events occurred in surrounding areas; (3) and species abundance maintained at >0.5×10 5 cells/L in the surrounding area. Nine high-risk species were screened out that can easily form colonies, clusters, and groups, including Thalassiosira diporocyclus , Thalassiosira subtilis , Noctiluca scintillans , Phaeocystis globosa , Pseudo-nitzschia pungens , Pseudo-nitzschia delicatissima , Skeletonema costatum , Skeletonema dohrnii , Paralia sulcata . Due to small cells or the formation of short chains, some dominant phytoplankton species, even those with advantages in abundance and occurrence, had difficulty threatening the reliability of cooling water systems in nuclear power plants. The outbreak of different phytoplankton species varied daily, and the risk of blockage was highest from April to July. The biological characteristics, ecological mechanisms underlying outbreaks of high-risk phytoplankton species are reviewed and discussed, suggesting a high degree of temporal and spatial variability of blockage risk. Finally, main prevention and control measures used against high-risk phytoplankton species are provided to imply new ideas and methods for nuclear power plants. These strategies have very important practical and scientific significance.

Sand barrier morphological evolution based on time series remote sensing images: a case study of Anhaiao, Pingtan - Heshan Lin; Xingguang Yu; Zhigang Yu; Yikang Gao; Jinyan Xu; Aiping Feng; Zhijun Liu; Degang Jiang; Fan Yu (Acta Oceanologica Sinica, 2020)

Chemical constituents from the bark of bauhinia purpurea and their NO inhibitory activities - Lin Ni; Wei Huang; Yan Shi; Heshan Wang; Yatie Qiu; Huiyou Xu (Natural Product Research, 2020)

Comprehensive Investigation and Assessment of Nutrient and Heavy Metal Contamination in the Surface Water of Coastal Bohai Sea in China - Heshan Lin; Hongjun Li; Xiaolong Yang; Zizhou Xu; Yindong Tong; Xingguang Yu (Journal of Ocean University of China, 2020)

Macrobenthic communities on the continental shelf of the Prydz Bay, East Antarctica - Kun Liu; Heshan Lin; Xuebao He; Yaqin Huang; Zhong Li; Junhui Lin; Jianfeng Mou; Shuyi Zhang; Jianjun Wang; Jun Sun (Acta Oceanologica Sinica, 2020)

Spatial variability of macrobenthic production in the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Junhui Lin; Yaqin Huang; Xuebao He; Zhong Li; Shuyi Zhang; Jianfeng Mou; Yanguang Liu; Puqing Song; Yu Wang; et al. (Polar Biology, 2019)

Spatial pattern of macrobenthic communities along a shelf-slope-basin transect across the Bering Sea - Heshan Lin; Kun Liu; Jianjun Wang; Yaqin Huang; Zhong Li; Junhui Lin; Xuebao He; Shuyi Zhang; Jianfeng Mou; Yu Wang; Bingpeng Xing (Acta Oceanologica Sinica, 2018)

An ecological survey of the abundance and diversity of benthic macrofauna in Indonesian multispecific seagrass beds - Junhui Lin; Yaqin Huang; Ucu Yanu Arbi; Heshan Lin; Muhammad Husni Azkab; Jianjun Wang; Xuebao He; Jianfeng Mou; Kun Liu; Shuyi Zhang (Acta Oceanologica Sinica, 2018)

Fouling community characteristics in subtropical coastal waters of the southwestern East China Sea - Heshan Lin; Jianjun Wang; Wei Liu; Kun Liu; Shuyi Zhang; Xuebao He; Yaqin Huang; Junhui Lin; Jianfeng Mou; Chengxing Zheng; Tao Yan (Acta Oceanologica Sinica, 2017)

Community structure and spatial-temporal variation of netz-phytoplankton in the Bering Sea in summer - Yu Wang; Peng Xiang; Youyin Ye; Gengming Lin; Qingliang Yang; Heshan Lin; Mao Lin (Acta Oceanologica Sinica, 2016)

A new deep-sea hydroid (Cnidaria: Hydrozoa) from the Bering Sea Basin reveals high genetic relevance to Arctic and adjacent shallow-water species - Xikun Song; Cinzia Gravili; Jianjun Wang; Yacheng Deng; Yongqiang Wang; Lu Fang; Heshan Lin; Shaoqing Wang; Yiting Zheng; Junhui Lin (Polar Biology, 2016)

Contamination of sulfonamide antibiotics and sulfamethazine-resistant bacteria in the downstream and estuarine areas of Jiulong River in Southeast China - Danyun Ou; Bin Chen; Renao Bai; Puqing Song; Heshan Lin (Environmental Science and Pollution Research, 2015)

Biodiversity and community structural characteristics of macrobenthos in the Chukchi Sea - Jianjun Wang; Heshan Lin; Xuebao He; Junhui Lin; Yaqin Huang; Rongguan Li; Chengxing Zheng; Fengwu Zheng; Jinxiang Jiang (Acta Oceanologica Sinica, 2014)

Community structure and spatial distribution of macrobenthos in the shelf area of the Bering Sea - Jianjun Wang; Xuebao He; Heshan Lin; Junhui Lin; Yaqin Huang; Chengxing Zheng; Fengwu Zheng; Rongguan Li; Jinxiang Jiang (Acta Oceanologica Sinica, 2014)

Effect of active immunization against a recombinant mouse granulocyte-macrophage colony-stimulating factor/somatostatin fusion protein on the growth of mice - Bingbing Wu; Ruili Qi; Bin Li; Taoyan Yuan; Heshan Liu; Jun He; Zhiwei Lin; Weifen Li; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)